AKTIVITAS BAWANG PUTIH (Allium sativum L.) SEBAGAI AGEN ANTIBAKTERI - Debi Kristiananda; Juvita Lisu Allo; Veronica Arien Widyarahma; Lusiana Lusiana; Jeanne Magistra Noverita; Florentinus Dika Octa Riswanto; Dewi Setyaningsih (Universitas Wahid Hasyim Semarang, 2022)
Garlic (Allium sativum L.) has various potentials in overcoming diseases, one of which is as an antibacterial. The purpose of this study was to explore, analyze and review the activity of garlic (Allium sativum L.) as an antibacterial agent. This study uses a literature search method using search sites such as Google Scholar, Pubmed, ScienceDirect, AYU, NCBI, Elsevier, PlosOne, and Google Scholar. by entering keywords such as antibacterial, Garlic, and Allium sativum L. Garlic contains secondary metabolites that function as antibacterial agents such as alkaloids, tannins, saponins, flavonoids, allicin. Garlic has been shown to inhibit the growth of gram-positive and negative bacteria species Escherichia, Salmonella, Staphylococcus, Streptococcus, Klebsiella, Proteus, Bacillus, Clostridium, P. aeruginosa, K. pneumoniae and, Bifidobacterium lactis predominantly using the paper disk and well diffusion method.